- 1-800-665-6601
- [email protected]

(x + 1) / (x ^2 + 2 x + 1) = (2 x – 3) / (x + 1)

i) Factorize the denominator of the L.H.S. rational expression

(x ^2 + 2 x + 1) = (x ^2 + 2 * x * 1 + 1^2) = (x + 1) ^2

ii) Now you can cancel out the numerator to the numerator and denominator to the denominator.

(x + 1) / (x ^2 + 2 x + 1) = (2 x – 3) / (x + 1)

(x + 1) / (x + 1) ^ 2 = (2 x – 3) / (x +1)

Cancel out (x + 1) from the numerator and denominator of the L.H.S. rational expression.

1 / (x + 1) = (2 x – 3) / (x + 1).

Again cancel out (x + 1) from the denominator of the L.H.S. and from denominator of the R.H.S.

1 = 2 x – 3

1+3 = 2x-3+3

4=2x

X=4

1/x=x/4

X^2 = 4

X= ± 2